The Exploration of Language Evolution: A Study of Linguistic Divergence and Kinship in the Provinces of Sumatra Island - Riska Meliana; Irfa Luthfia Rahmani; Ana Yuliana; Rizqi Wafi (Linguistik Indonesia, 2026)
This research investigates language evolution and linguistic kinship on the island of Sumatra. It also extends coverage to cognate languages in other regions. The languages studied include those spoken by various ethnic groups, namely Aceh, Gayo (Aceh), Batak Toba, Mandailing (North Sumatra), Rejang, Serawai (Bengkulu), Melayu Bangka, and Kayu Agung (Bangka Belitung). The main objectives are (1) to investigate how quantitative and qualitative analyses reveal kinship relationships between Acehnese (AT) and Gayo (GT) in Aceh, Batak Toba (BTT) and Batak Mandailing (BMT) in North Sumatra, Rejang (RT) and Serawai (ST) in Bengkulu, and Melayu Bangka (MBT) and Kayu Agung (KAT) in Bangka Belitung; (2) to identify and present empirical evidence to determine the divergence time for each language pair, and (3) to classify the studied languages into specific kinship groups and to identify the proportions of kinship relationships among languages in Aceh, North Sumatra, Bengkulu, and Bangka Belitung. This research used the lexicostatistical and glottochronological methods developed by Swadesh. Word kinship was evaluated using a list of 200 words. The results showed significant differences among the eight languages. The languages in North Sumatra Province and Bengkulu, for example, had a low similarity rate of 17%. The kinship percentage of local languages in Bengkulu and Bangka Belitung provinces averaged 50.5%. This places them in the “Language of Family” category, indicating a correlation in vocabulary despite variations in phonetic elements and dialects. Glottochronological calculations estimate the time of separation between the languages to range from 430 BC to 3,590 AD. This research makes a significant contribution and plays a vital role in supporting language documentation and preservation. It also helps to understand the social and cultural dynamics that influence language development in society.